Three-dimensional ordered macroporous / mesoporous multi-component catalyst for preparing butadiene through dehydrogenation of butylene oxide by carbon dioxide, and preparation and application of three-dimensional ordered macroporous / mesoporous multi-component catalyst
By using a three-dimensional ordered macroporous mesoporous multicomponent catalyst in the CO2 butene oxide dehydrogenation reaction, low catalytic performance and low catalytic performance are solved by using the framework domain confining strategy and alumina support and active components of iron, vanadium and chromium oxides. The problem of insufficient selectivity of butadiene has achieved efficient butadiene production.
Patent Information
- Application Number
- CN202411517012.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2024-12-31
Smart Images

Figure FT_1 
Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to a three-dimensional ordered macroporous and mesoporous multi-component catalyst and a preparation method thereof, which is mainly used for CO2 oxidation of butene to dehydrogenate to prepare 1,3-butadiene, and belongs to the field of catalysts and engineering technology. Technical Background
[0002] As an important raw material for the petrochemical industry, 1,3-butadiene is widely used in the production of many chemicals such as cyclopentane, cyclooctadiene, tetrahydrofuran, etc., in addition to being used to produce products such as rubber, plastics and resins. It has high application value. In recent years, with the development of the economy, China's demand and consumption of butadiene have increased significantly. At present, butadiene is in short supply in the market, while 1-butene, as a raw material for butadiene synthesis, is in a state of overcapacity. A large amount of 1-butene has not been effectively utilized and is often burned as fuel, which increases carbon emissions. The use of CO2 as an oxidant to produce 1,3-butadiene by oxidative dehydrogenation of 1-butene meets the requirements of green chemical processes and has attracted widespread attention. This process can not only convert low-value 1-butene into 1,3-butadiene with higher added value, but also convert CO2 into CO, realizing the high-value utilization of C1 resources.
[0003] Metal iron salt catalysts are widely used in the oxidative dehydrogenation of 1-butene to butadiene due to their low price and excellent performance, but the performance of single iron-based catalysts is not ideal. Therefore, the development of multi-component catalysts has become the most important way to improve the performance of oxidative dehydrogenation. The catalytic performance of a catalyst depends on the structure of the catalyst, the dispersion of the active species and the mobility of the oxygen species. The lattice oxygen in iron oxides often plays an important role in oxidative dehydrogenation reactions. However, the activation of lattice oxygen in a tetrahedral structure is often difficult, which greatly limits the oxidative dehydrogenation performance of the catalyst. The construction of a multi-component catalyst can distort the lattice of iron oxide by introducing other active components. At the same time, as the electron transfer effect between the active components is enhanced, the lattice oxygen is more easily activated, thereby improving the oxidative dehydrogenation performance of the catalyst. In the catalyst prepared by the traditional impregnation method, the binding force between the carrier and the metal active component is weak, and there are problems such as uneven distribution of the active components and the easy aggregation of the active components into larger particles at high temperatures, which reduces the catalytic performance of the catalyst or even deactivates it. The skeleton confinement strategy limits the freedom of molecules or nanoparticles in space by constructing a skeleton with a specific structure, preventing the aggregation of active components in the form of a physical barrier, and creating more active interfaces to the maximum extent. Therefore, the use of skeleton confinement can improve the dispersion of active components, and the skeleton confinement effect can prevent further aggregation of active components during the reaction process.
[0004] Patent CN 115400748 B discloses a method for preparing a vanadium-based catalyst for the reaction of isobutane CO2 oxidative dehydrogenation to isobutene. The patent points out that the carrier material has an important influence on the catalytic performance. Traditional zeolite molecular sieves are prone to carbon-carbon bond breakage due to excessive exposure of strong acid sites inside them, and the narrow and long micropore channels easily cause isomerization reaction during the passage of isobutene, thereby resulting in a decrease in isobutene selectivity. At the same time, the catalyst exhibits excellent anti-carbon deposition performance, high isobutane conversion rate, and high isobutene selectivity. However, the catalyst of this patent is prepared by an impregnation method, and the active components are prone to agglomeration into larger particles, thereby increasing the probability that the catalyst adsorbs multiple olefin molecules and condenses into a regular graphite structure through polymerization or cyclization reaction, thereby resulting in a higher carbon deposition rate.
[0005] Patent CN 106607030 B discloses a catalyst and a process for the oxidative dehydrogenation of butene to butadiene. The catalyst introduces metal oxides such as Li, Sb and Ga to regulate the electronic structure of the iron-based catalyst, and simultaneously achieves a clever balance between the selective oxidation of butene and the activation of oxygen, thereby obtaining a higher butadiene selectivity and yield. However, the catalyst is an iron oxide lacking a catalyst carrier, and is not suitable for industrial applications due to its high cost.
[0006] In summary, the catalysts reported in existing patents are prone to isomerization of n-butene due to the narrow and long micropores, which leads to a decrease in butadiene selectivity. The patent of this invention prepares a three-dimensional ordered macroporous mesoporous material with good thermal stability and large specific surface area. This unique texture characteristic makes the active species highly dispersed, and the reactants and products can diffuse in time. At the same time, the use of the skeleton confinement method can enhance the interaction between the active components and effectively improve the catalyst butadiene selectivity and yield. Summary of the invention
[0007] The invention provides a method for preparing a catalyst for preparing butadiene by dehydrogenating butene through CO2 oxidation. The catalyst can not only prepare butadiene by dehydrogenating butene through CO2 oxidation, but also has a high 1,3-butadiene yield and selectivity. The preparation process is simple and the catalyst is suitable for industrial production and application.
[0008] The preparation method of the Fe-based catalyst for the dehydrogenation of butene to butadiene by CO2 oxidation of butene of the present invention comprises the following steps: (1) Dissolve methyl methacrylate and potassium persulfate in water, stir and react at 50-90° C. under nitrogen atmosphere for 0.5-6 hours, filter and centrifuge to obtain polymethyl methacrylate, wherein the mass ratio of methyl methacrylate to potassium persulfate is 1000:1-1000:0.1.
[0009] (2) Dissolve a structure directing agent, aluminum isopropoxide and concentrated nitric acid in anhydrous ethanol and stir them thoroughly to obtain a uniform and transparent solution A; the structure directing agent is at least one of the triblock copolymers P123 or F127; the mass ratio of the structure directing agent to nitric acid is 1:0.1 to 1:50; the mass ratio of the structure directing agent to aluminum isopropoxide is 1:0.1 to 1:10.
[0010] (3) Dissolve the active component precursor salt in anhydrous ethanol and stir thoroughly to obtain a uniform solution B. The active component precursor salt is an iron salt, a chromium salt and a vanadium salt, wherein the iron salt is at least one of iron nitrate and iron acetate, the chromium salt is at least one of chromium nitrate and chromium acetate, and the vanadium salt is at least one of ammonium metavanadate and ammonium orthovanadate.
[0011] (4) Slowly pour solution B into solution A and stir at 20-60°C for 6-18 hours to form a mixed solution C.
[0012] (5) The mixed solution C is impregnated into a methyl methacrylate template and then placed in a forced air drying oven at 40-80°C for 20-48 hours to obtain a block. The main purpose of impregnating the solution into the methyl methacrylate template is to obtain a three-dimensional ordered macroporous structure.
[0013] (6) The dried mass is calcined in a muffle furnace at 500-800°C for 2-5 hours in an air atmosphere, cooled to room temperature, and crushed to obtain a catalyst.
[0014] The catalyst prepared by the present invention consists of two parts: carrier alumina and active component metal oxide. The alumina carrier accounts for 70% to 90% of the total mass of the catalyst; the active component metal oxide is iron oxide, vanadium oxide and chromium oxide, the active component iron oxide accounts for 8-20%, vanadium oxide and chromium oxide each account for 1-5%.
[0015] The three-dimensional ordered macroporous mesoporous multi-component catalyst of the present invention is used for the CO2 oxidation dehydrogenation of butene to butadiene reaction. Under the catalysis of the three-dimensional ordered macroporous mesoporous multi-component catalyst, 1-butene and CO2 mixed gas (1-butene and CO2 mixed gas volume ratio is 1:9) react to produce butadiene; at an air velocity of 4.5 g / (g cat •h), when the reaction temperature is 600℃, the butadiene yield is greater than 25% and the butadiene selectivity is greater than 29%.
[0016] The present invention has the following advantages over the prior art: 1. The catalyst prepared by the present invention has the characteristics of three-dimensional ordered macropores and ordered mesopores. First, the ordered macroporous mesoporous structure and the large specific surface area enable the metal oxide to be evenly dispersed on the carrier, providing abundant active sites for the reaction and thus improving the catalytic activity. Secondly, this ordered macroporous mesoporous structure can increase the contact area between the reactants and the catalyst, which helps to promote the mass transfer process of the reactants and products, accelerate the catalytic reaction, increase the reaction rate, and make the catalytic performance more efficient. Finally, this ordered macroporous mesoporous structure can reduce the problem of decreased butadiene selectivity caused by the isomerization of n-butene caused by the narrow and long micropore channels.
[0017] 2. The active components of the catalyst prepared by the present invention are multi-component (including Fe, Cr, V), which solves the problem of low selectivity and yield of butadiene in single-component iron-based catalysts. At the same time, the catalyst with a multi-level pore structure prepared by the skeleton confinement method prevents the aggregation of active components in the form of a physical barrier, creates more active interfaces to the maximum extent, and also avoids the waste of active components caused by agglomeration. The synergistic effect between multiple components accelerates the flow of electrons between components, enhances the redox performance of the catalyst, and promotes the activation of lattice oxygen in the catalyst, thereby accelerating the dehydrogenation process of 1-butene, so that the catalyst exhibits more excellent catalytic performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is a transmission electron microscope image of the catalyst in Example 1. DETAILED DESCRIPTION
[0019] The preparation method and application performance of the catalyst of the present invention are further described below through specific examples.
[0020] Example 1 (1) Dissolve 100 g of methyl methacrylate and 0.4 g of potassium persulfate in 300 ml of water in a three-necked flask and condense at 60 °C under nitrogen atmosphere. o C in a water bath and stirred for 0.5 hours, and polymethyl methacrylate was obtained by filtration and centrifugation; (2) Dissolve 10 g P123, 10.84 g aluminum isopropoxide and 9 ml concentrated nitric acid in 50 ml anhydrous ethanol and stir thoroughly to obtain a uniform and transparent solution A. (3) Dissolve 6.5 g of ferric nitrate, 4.3 g of ammonium metavanadate and 3.3 g of chromium acetate in 50 ml of anhydrous ethanol and stir thoroughly to obtain a uniform solution B; (4) Slowly pour solution B into solution A. o C in a water bath and stirred thoroughly for 0.5 hours to form a mixed solution C; (5) Pour the mixed solution C into the prepared polymethyl methacrylate template and place it in a 40 o C oven for 10 hours to obtain a flake; (6) The dried flakes were placed in a muffle furnace under air atmosphere at 500 o C was calcined for 2 hours, cooled to room temperature, and crushed to obtain the catalyst. The catalyst was pressed into tablets and sieved to obtain catalyst particles of 40 mesh, which were marked as cat-1.
[0021] (7) Catalytic performance: The catalytic performance of the CO2 oxidation of butene to butadiene on the catalyst was evaluated using a continuous fixed bed reactor. 0.1 g to 5.0 g of catalyst and 0.2 g to 5.1 g of quartz sand were loaded into the constant temperature section of the reactor, and then nitrogen was introduced at a ventilation rate of 60 ml / min. The reactor began to heat up to 600 °C. After the fixed bed was heated to 600 °C, a mixture of n-butene and CO2 was introduced into the constant temperature section of the fixed bed reactor at a ventilation rate of 60 ml / min in a ratio of 1:9, and the mixture was heated to 4.5 g / (g cat ·h) of mass space velocity through the reactor until 1,3-butadiene product appears to terminate the catalytic reaction. The reactants and products are analyzed by an online GC9790 Plus gas chromatograph with FID detector and TCD detector. 1-Butene is used as a model reactant molecule to evaluate the oxidative dehydrogenation performance of the catalyst in a continuous fixed bed reactor. The catalytic performance test of catalyst cat-1 is shown in Table 1.
[0022] Example 2 (1) Dissolve 90 g of methyl methacrylate and 0.3 g of potassium persulfate in 300 ml of water in a three-necked flask and condense at 70 °C under nitrogen atmosphere. o C in a water bath and stirred for 1 hour, and polymethyl methacrylate was obtained by filtration and centrifugation; (2) Dissolve 9 g F127, 9.84 g aluminum isopropoxide and 8 ml concentrated nitric acid in 45 ml anhydrous ethanol and stir thoroughly to obtain a uniform and transparent solution A. (3) Dissolve 6 g of ferric acetate, 4 g of ammonium metavanadate and 3 g of chromium acetate in 45 ml of anhydrous ethanol and stir thoroughly to obtain a uniform solution B; (4) Slowly pour solution B into solution A at 25 o C in a water bath and stir thoroughly for 1 hour to form a mixed solution C; (5) Pour the mixed solution C into the prepared polymethyl methacrylate template and place 50 o C oven for 20 hours to obtain a flake; (6) The dried flakes were placed in a muffle furnace at 550°C under air atmosphere. oC was calcined for 2.5 hours, cooled to room temperature, and crushed to obtain the catalyst. The catalyst was pressed into tablets and sieved to obtain catalyst particles of 45 mesh, which were marked as cat-2.
[0023] (7) The catalyst performance test method is the same as in Example 1. The catalytic performance of catalyst cat-2 is shown in Table 1.
[0024] Example 3 (1) Dissolve 80 g of methyl methacrylate and 0.25 g of potassium persulfate in 300 ml of water in a three-necked flask and condense at 80 °C under nitrogen atmosphere. o C in a water bath and stirred for 2 hours, and polymethyl methacrylate was obtained by filtration and centrifugation; (2) Dissolve 8 g F127, 8.84 g aluminum isopropoxide and 7 ml concentrated nitric acid in 40 ml anhydrous ethanol and stir thoroughly to obtain a uniform and transparent solution A. (3) Dissolve 5.5 g of ferric nitrate, 3.7 g of ammonium orthovanadate, and 3.7 g of chromium nitrate in 20 ml of anhydrous ethanol and stir thoroughly to obtain a uniform solution B; (4) Slowly pour solution B into solution A at 40 o C in a water bath and stir thoroughly for 1.5 hours to form a mixed solution C; (5) Pour the mixed solution C into the prepared polymethyl methacrylate template and place it in a 60 o C oven for 30 hours to obtain a flake; (6) The dried flakes were placed in a muffle furnace under air atmosphere at 600 o C was calcined for 3 hours, cooled to room temperature, and crushed to obtain the catalyst. The catalyst was pressed into tablets and sieved to obtain catalyst particles of 50 mesh, which were marked as cat-3.
[0025] (7) The catalyst performance test method is the same as in Example 1. The catalytic performance of catalyst cat-3 is shown in Table 1.
[0026] Example 4 (1) Dissolve 70 g of methyl methacrylate and 0.2 g of potassium persulfate in 300 ml of water in a three-necked flask and condense at 90 °C under nitrogen atmosphere. o C in a water bath and stirred for 3 hours, and polymethyl methacrylate was obtained by filtration and centrifugation; (2) Dissolve 4 g P123 and 3 g F127, 7.84 g aluminum isopropoxide and 6 ml concentrated nitric acid in 30 ml anhydrous ethanol and stir thoroughly to obtain a uniform and transparent solution A. (3) Dissolve 5 g of ferric acetate, 3.4 g of ammonium orthovanadate and 3.4 g of chromium nitrate in 35 ml of anhydrous ethanol and stir thoroughly to obtain a uniform solution B; (4) Slowly pour solution B into solution A at 50 o C in a water bath and stir thoroughly for 2 hours to form a mixed solution C; (5) Pour the mixed solution C into the prepared polymethyl methacrylate template and place it in a 60 o C oven for 24 hours to obtain a flake; (6) The dried flakes were placed in a muffle furnace at 650 °C under air atmosphere. o C was calcined for 3.5 hours, cooled to room temperature, and crushed to obtain the catalyst. The catalyst was pressed into tablets and sieved to obtain catalyst particles of 55 mesh, which were marked as cat-4.
[0027] (7) The catalyst performance test method is the same as in Example 1. The catalytic performance of catalyst cat-4 is shown in Table 1.
[0028] Example 5 (1) Dissolve 60 g of methyl methacrylate and 0.15 g of potassium persulfate in 300 ml of water in a three-necked flask and condense at 80 °C under nitrogen atmosphere. o C in a water bath for 4 hours, and then filtered and centrifuged to obtain polymethyl methacrylate; (2) Dissolve 6 g P123, 6.84 g aluminum isopropoxide and 5 ml concentrated nitric acid in 25 ml anhydrous ethanol and stir thoroughly to obtain a uniform and transparent solution A. (3) Dissolve 2.5 g of ferric nitrate, 2 g of ferric acetate, 3 g of ammonium orthovanadate and 3 g of chromium nitrate in 30 ml of anhydrous ethanol and stir thoroughly to obtain a uniform solution B; (4) Slowly pour solution B into solution A at 60 o C in a water bath and stir thoroughly for 3 hours to form a mixed solution C; (5) Pour the mixed solution C into the prepared polymethyl methacrylate template and place it in 80 o C oven for 30 hours to obtain a flake; (6) The dried flakes were placed in a muffle furnace at 750 °C under air atmosphere. o C was calcined for 3.5 hours, cooled to room temperature, and crushed to obtain the catalyst. The catalyst was pressed into tablets and sieved to obtain catalyst particles of 60 mesh, which were marked as cat-5.
[0029] (7) The catalyst performance test method is the same as in Example 1. The catalytic performance of catalyst cat-5 is shown in Table 1.
[0030] Comparative Example 1 (1) Dissolve 50 g of methyl methacrylate and 0.12 g of potassium persulfate in 300 ml of water in a three-necked flask and condense at 70 °C under nitrogen atmosphere.o C in a water bath and stirred for 5 hours, and polymethyl methacrylate was obtained by filtration and centrifugation; (2) Dissolve 5 g P123, 5.84 g aluminum isopropoxide and 4 ml concentrated nitric acid in 20 ml anhydrous ethanol and stir thoroughly to obtain a uniform and transparent solution A. (3) Dissolve 3 g of ferric nitrate in 25 ml of anhydrous ethanol and stir thoroughly to obtain a uniform solution B; (4) Slowly pour solution B into solution A at 50 o C in a water bath and stirred for 5 hours to form a mixed solution C; (5) Pour the mixed solution C into the prepared polymethyl methacrylate template and place it in a 60 o C oven for 40 hours to obtain a flake; (6) The dried flakes were placed in a muffle furnace under air atmosphere at 800 o C was calcined for 4 hours, cooled to room temperature, and crushed to obtain the catalyst. The catalyst was pressed into tablets and sieved to obtain catalyst particles of 70 mesh, which were marked as cat-6.
[0031] (7) The catalyst performance test method is the same as in Example 1. The catalytic performance of catalyst cat-6 is shown in Table 1.
[0032] Comparative Example 2 (1) Dissolve 40 g of methyl methacrylate and 0.1 g of potassium persulfate in 300 ml of water in a three-necked flask and condense at 60 °C under nitrogen atmosphere. o C in a water bath and stirred for 6 hours, and polymethyl methacrylate was obtained by filtration and centrifugation; (2) Dissolve 4 g P123, 4.84 g aluminum isopropoxide and 3 ml concentrated nitric acid in 25 ml anhydrous ethanol and stir thoroughly to obtain a uniform and transparent solution A. (3) Pour solution A into the prepared polymethyl methacrylate template and place it in a 70 o C oven for 48 hours to obtain a flake; (4) The dried flakes were placed in a muffle furnace under air atmosphere at 800 o C was calcined for 5 hours and cooled to room temperature to obtain Al2O3; (4) Dissolve 2 g of ferric acetate, 1 g of chromium nitrate and 1 g of ammonium metavanadate in 20 ml of anhydrous ethanol and stir thoroughly to obtain a uniform solution B; (5) Add solution B to the prepared Al2O3 and stir for 3 hours, then place in an oven at 80°C and dry for 24 hours; (6) The dried flakes were placed in a muffle furnace under air atmosphere at 800 oC was calcined for 5 hours, cooled to room temperature, and crushed to obtain a catalyst; the catalyst was pressed into tablets and sieved to form catalyst particles of 80 mesh, which were marked as cat-7.
[0033] (7) The catalyst performance test method is the same as in Example 1. The catalytic performance of catalyst cat-7 is shown in Table 1.
[0034] Note: This data is for the test reaction temperature of 600 o C time test results for the first 20 minutes.
[0035] Depend on Figure 1 It can be seen that the regular and orderly macroporous-mesoporous structure indicates that the present invention successfully prepares a three-dimensional ordered macroporous mesoporous catalyst. Compared with Comparative Example 1, the multi-component catalyst prepared in Example 1 shows more excellent performance in terms of 1-butene conversion rate, butadiene yield and butadiene selectivity (butadiene yield is greater than 25%, butadiene selectivity is greater than 29%). At the same time, compared with the catalyst prepared by the impregnation method (Comparative Example 2), the catalyst prepared by the skeleton confinement method shows better catalytic performance. It can be seen that the catalyst prepared by the patent of the present invention has excellent catalytic performance in the CO2 oxidation of butene dehydrogenation to butadiene reaction.
Claims
1. A three-dimensional ordered macroporous and mesoporous multi-component catalyst for the dehydrogenation of butene to butadiene by CO2 oxidation, characterized in that: The catalyst is composed of carrier alumina and active component metal oxides, wherein the carrier alumina accounts for 70% to 90% of the total mass of the catalyst; the active component metal oxides are iron oxides, vanadium oxides and chromium oxides, wherein the iron oxides, vanadium oxides and chromium oxides account for 8-20%, 1-5% and 1-5% of the total mass of the catalyst respectively; The preparation method of the catalyst comprises the following steps: (1) dissolving methyl methacrylate and potassium persulfate in water, stirring and reacting in a water bath at 50-90° C. under a nitrogen atmosphere for 0.5-6 hours, filtering and centrifuging to obtain polymethyl methacrylate; (2) dissolving the structure directing agent, aluminum isopropoxide and concentrated nitric acid in anhydrous ethanol and stirring them thoroughly to obtain a uniform and transparent solution A; (3) Dissolving the active component precursor salt in anhydrous ethanol and stirring thoroughly to obtain a uniform solution B; (4) Slowly pour solution B into solution A and stir thoroughly to form a mixed solution C; (5) The mixed solution C is immersed in polymethyl methacrylate and placed in an oven to dry to obtain a block; (6) The dried mass is calcined in an air atmosphere in a muffle furnace, cooled to room temperature, and crushed to obtain a catalyst.
2. The three-dimensional ordered macroporous and mesoporous multi-component catalyst for preparing butadiene by dehydrogenation of butene by CO2 oxidation as claimed in claim 1, characterized in that: In step (1), the mass ratio of methyl methacrylate to potassium persulfate is 1000:1 to 1000:0.
1.
3. The three-dimensional ordered macroporous and mesoporous multi-component catalyst for preparing butadiene by dehydrogenation of butene by CO2 oxidation as claimed in claim 1, characterized in that: In step (2), the structure directing agent is at least one of the triblock copolymers P123 and F127; the mass ratio of the structure directing agent to nitric acid is 1:0.1 to 1:50; and the mass ratio of the structure directing agent to aluminum isopropoxide is 1:0.1 to 1:
10.
4. The three-dimensional ordered macroporous and mesoporous multi-component catalyst for preparing butadiene by dehydrogenation of butene by CO2 oxidation as claimed in claim 1, characterized in that: In step (3), the active component precursor salt is an iron salt, a chromium salt and a vanadium salt, wherein the iron salt is at least one of iron nitrate and iron acetate, the chromium salt is at least one of chromium nitrate and chromium acetate, and the vanadium salt is at least one of ammonium metavanadate and ammonium orthovanadate.
5. The three-dimensional ordered macroporous and mesoporous multi-component catalyst for preparing butadiene by dehydrogenation of butene by CO2 oxidation as claimed in claim 1, characterized in that: In step (4), sufficient stirring means stirring at 20-60° C. for 6-18 hours.
6. The three-dimensional ordered macroporous and mesoporous multi-component catalyst for preparing butadiene by dehydrogenation of butene by CO2 oxidation as claimed in claim 1, characterized in that: In step (5), the drying process is carried out in a forced air drying oven at 40-80° C. for 20-48 hours.
7. The three-dimensional ordered macroporous and mesoporous multi-component catalyst for preparing butadiene by dehydrogenation of butene by CO2 oxidation as claimed in claim 1, characterized in that: In step (6), the calcination process is performed at 500-800° C. for 2-5 hours.
8. Use of the three-dimensional ordered macroporous and mesoporous multi-component catalyst as claimed in claim 1 in the CO2 oxidation of butene to butadiene.
9. Use of the three-dimensional ordered macroporous mesoporous multi-component catalyst according to claim 1 in CO2 oxidation of butene to butadiene by dehydrogenation, characterized in that: Under the catalysis of three-dimensional ordered macroporous mesoporous multi-component catalyst, 1-butene and CO2 mixed gas reacted to produce butadiene; the space velocity was 4.5 g / (g cat •h), the reaction temperature is 600℃, and the volume ratio of 1-butene and CO2 mixed gas is 1:9.
Citation Information
Patent Citations
Catalyst used for preparing butadiene through butene oxidative dehydrogenation, and application thereof
CN105582953A
High-efficiency catalyst for preparing 1,3-butadiene by using carbon dioxide to oxidize 1-butene to dehydrogenate and preparation method thereof
CN109647400A
Catalyst for oxidative dehydrogenation and method of preparing the same
US20180290126A1